Liposome-encapsulated AICAR hydrogel regulates macrophage metabolic reprogramming via SIK1 activation to alleviate osteoarthritis - Yong Fu; Jiahui Hou; Qinmeng Yang; Yanpeng Lin; Nie Rui; Jun Wang; Hangtian Wu; Bin Yu (Journal of Nanobiotechnology)
Abstract Background Osteoarthritis (OA), the most prevalent joint disorder, is characterized by a complex etiology and a lack of safe and effective therapeutic interventions. Emerging evidence suggests that immune cell dysregulation plays a pivotal role in the pathogenesis of OA. Recent advancements in high-throughput sequencing technologies, along with the integration of machine learning into medical research, have provided novel insights into the molecular mechanisms underlying various diseases. However, the specific roles and mechanisms of immune-related factors in OA remain poorly understood. This study aims to identify potential biomarkers for the diagnosis and monitoring of OA progression and to explore targeted therapeutic strategies based on key genes associated with the disease. Results WGCNA and immune infiltration analysis identified SIK1 as a core gene involved in immune regulation during the progression of OA. In vitro experiments demonstrated that AICAR, an activator of SIK1, significantly suppressed inflammatory responses by modulating glucose and lipid metabolism in macrophages. A novel nanoliposome composite hydrogel, Gel@Lipo@AICAR, has been successfully developed for the targeted delivery of AICAR. The intra-articular administration of Gel@Lipo@AICAR demonstrated excellent biosafety and therapeutic potential in mitigating the progression of OA. Conclusions This study identifies SIK1 as a novel biomarker for diagnosing and monitoring the progression of OA. The anti-inflammatory effects of its agonist, AICAR, were validated, underscoring its role in reprogramming macrophage glucose and lipid metabolism. Furthermore, the development of Gel@Lipo@AICAR, a nanoliposome composite hydrogel, presents a promising therapeutic strategy for the treatment of OA. Graphical Abstract Preparation of Gel@Lipo@AICAR and therapeutic efficacy in ACLT osteoarticular model mice